Cabinets of Curiosity: Fear and Metaphor in Cyberspace - Harding, Judith (Proceedings of the International Conference on Networked Learning, 2006)
Drawing on current debates on embodiment, uses of networked learning, dialogical strategies in higher education teaching, and the force of metaphor and visual analogy, this paper will explore some diverse critical discussions of emotional responses to the internet. These may suggest some possible new approaches to conceptualising the role of networked learning in the landscape of higher education academic practice. The paper will also track the journey of one academic from entrenched sceptic to committed enthusiast through recognition of the imaginative possibilities of internet-based connection. This worked chiefly through being introduced to the extensive theoretical and philosophical literature related to internet use, and the development of new forms of writing that take advantage of the new opportunities the web offers to make imaginative metaphorical connections and explore personal histories. These new forms are informed by historical antecedents of the use of visual mnemonic and embodied learning.